マーキアインはHeLa細胞においてデキサメタゾン刺激に伴うERK脱リン酸化の亢進を増強しヒスタミンH1受容体遺伝子発現を抑制する - 河井, 真季子; 北村, 嘉章; 武田, 憲昭; 福井, 裕行; 給田, 愛結美; 中野, 誠一; 岡島, 菜津希; 水口, 博之 (日本薬理学会年会要旨集, 2019)
As the expression level of a disease-sensitive gene is correlated with the symptom severity, suppression of its gene expression should be good therapeutics. We demonstrated that histamine H1 receptor (H1R) gene is an allergic rhinitis (AR)-sensitive gene. We isolated maackiain (MCN) from Kujin that suppresses H1R gene up-regulation. We also showed that MCN bound to Hsp90 and disrupts the interaction between PKCδ and Hsp90, suggesting MCN modulates steroid signaling. Western blot analysis showed that MCN completely inhibited ERK phosphorylation although the inhibition of PKC dphosphorylation was partial, suggesting that MCN suppresses H1R gene expression by the additional mechanism. MCN enhanced dexamethasone-activated GRE promoter activity. MCN also enhanced dexamethasone-induced gene up-regulation for dual-specificity phosphatase 1 (DUSP1), that dephosphorylizes ERK. On the other hand, dexamethasone suppressed H1R gene up-regulation. These findings suggest that MCN suppresses H1R gene expression through not only the disruption of interaction between PKCδ and Hsp90 but also the activation of ERK dephosphorylation by the enhancement of dexamethasone-induced DUSP1 gene expression.